Fabrication of gelatin-EGCG-pectin ternary complex stabilized W/O/W double emulsions by ultrasonic emulsification: Physicochemical stability, rheological properties and structure. (February 2023) - Huang, Xiang; Tu, Rui; Song, Hongbo; Dong, Kai; Geng, Fang; Chen, Lei; Huang, Qun; Wu, Yingmei
Abstract: Double emulsions have very promising application prospects in the pharmaceutical, cosmetic, and food industries. Nevertheless, its usage in the food industry is restricted mainly due to its immense stability problems. Here, W1 /O/W2 double emulsion was prepared by two-step emulsification method using ultrasonic emulsification technology. The physicochemical stability, rheological properties, thermal stability, and microstructure of the double emulsion were investigated. The results revealed that W1 /O/W2 double emulsion with optimum stability was prepared on the parameters that the ratio of W1 (gelatin)/O primary emulsion to the external aqueous phase (gelatin-EGCG-high methoxyl pectin ternary complex) was 6:4, ultrasonic power was 80 W, ultrasonic time was 6 min, and ternary complex concentration was 0.75%. The double emulsion produced under these conditions had the smallest particle size (1143 nm) and the maximum absolute zeta potential value (39.17 ± 0.50 mV). The results of full-featured stability analyzer manifested that the emulsion system no longer underwent phase separation. Confocal laser scanning microscopy (CLSM) successfully observed a uniformly dispersed double emulsion. Furthermore, dynamic rheological properties demonstrated that the cohesive strength of W1 /O/W2 double emulsion was strength than that of W1 /O primary emulsion. Differential scanning calorimetry (DSC) analysis suggested that both remained stable throughout the temperature change, while the W1 /O/W2 double emulsion was more thermally stable. Hence, the gelatin-EGCG-high methoxyl pectin ternary complex can act as an effective emulsion stabilizer to stabilize the W1 /O/W2 double emulsion. Graphical abstract: Image 1 Highlights: W/O/W double emulsions were prepared by ultrasonic emulsification method. Ultrasonic treatment improves the physical stability of the emulsion. The optimally stable double emulsion system no longer exhibits phase separation. Ternary complex can be used as emulsion stabilizer to stabilize double emulsion. Cohesive strength of the double emulsion is enhanced after ultra-sonication.